HRM PRACTICES ACROSS DIFFERENT CULTURES: AN EVIDENCE-BASED STUDY IN CANADA AND JAPAN - I Made Dewa Ardianata; Diva Suncoko; Muhammad Faris Fadli; Raihan Naufal Aulia; Sandra Hanum Salsabilla; Raudotul Jannah (Lavish Opulent Education, 2024)
This paper specifically aims to conduct a comprehensive and in-depth analysis of human resource management (HRM) practices in Canada and Japan, with a view to exploring the extent to which culture, social values, history and societal context influence HRM policies and implementation in both countries. This study has used method with a descriptive-qualitative approach was strictly applied to collect empirical data from various relevant secondary references. The data collected covered key aspects of HRM, such as recruitment, selection, training, compensation, Occupational Health and Safety (OHS), and termination of employment. Data analysis was conducted comparatively, focusing on identifying differences, similarities, and common patterns of HRM practices. The results show that HRM in Canada is significantly influenced by social aspirations for inclusiveness, diversity, and equal opportunity, which are reflected in its multidimensional and accommodating employee recruitment, selection, and training systems. On the other hand, HRM in Japan is deeply rooted in a culture of collectivism, group harmony, and organizational loyalty, which is reflected in training programs, compensation schemes, and layoff policies that emphasize collaboration and the sustainability of long-term employment relationships. A deep understanding of the influence of cultural and historical context on the formation of a country's HRM system. This understanding becomes the basis for the development of HRM models and policies that are adaptive and resilient in the face of globalization dynamics, applicable to the context of societies with similar characteristics in other countries.